Desenvolvimento de métodos analíticos para determinação de impurezas em produtos farmacêuticos - Mattiazzi, Patricia (2019)
The presence of impurities in medicinal products is usually associated with their presence in the raw material and/or the production process of the drug itself. The presence of these impurities raises concern, not only because of the inherent toxicity of certain contaminants but also because of the adverse effect that contaminants may have on drug stability and shelf-life. The objective of this work was to develop analytical methods for the determination of elemental impurities as well as titanium dioxide in pharmaceutical products using the Atomic Absorption Spectrometry technique. The presence of organic impurities in drugs of continuous use was also investigated. The analyses were performed on three drugs: losartan potassium, omeprazole and simvastatin, and five samples of each drug were obtained, the reference drug and four generic samples. For the titanium analysis, a total of 39 samples were evaluated. The techniques used for the development of the work were High Resolution Atomic Absorption Spectrometry with Continuous Source equipped with Graphite Furnace (HR-CS GFAAS) for the determination of lead, cadmium, iridium, palladium, platinum, rhodium, ruthenium, chromium, molybdenum, nickel, vanadium and copper; Flame-equipped Atomic Absorption Spectrometry (FAAS) for determination of titanium; Hydrogen Generation (HGAAS) for the analysis of arsenic; High Performance Liquid Chromatography (HPLC) for the determination of organic impurities and the assay of active principles. The methods were optimized and validated according to respective monographs described in the United States Pharmacopoeia (USP). The validated parameters were linearity, concentration range, precision, accuracy, limit of detection, limit of quantification and specificity. The proposed methods have met the requirements stipulated by the USP Chapter <233>, thus becoming equivalent to the procedure proposed by the compendium. Due to the characteristics of the HR-CS GFAAS, a screening method was proposed for the elements Pb, Cd, Ir, Pd, Pt, Rh, Ru, Cr, Mo, Ni, V and Cu. Through the analysis of the spectra it was possible to establish a "pass/fail" test to define the presence of the element in the sample. Only the elements Ni, Cr and Cu "fail" in the test and therefore were quantified. Arsenic was also detected in the samples, but the levels found did not exceed the limits stipulated by Chapter <232> for the 4 elements. No organic impurities were detected in the samples of losartan potassium and simvastatin. In omeprazole, two unidentified peaks were detected, but the levels found were below the limits stipulated by the USP. In the assay of the active ingredients, 3 samples of losartan potassium showed results below the limit. The method developed for Ti fulfilled the validation requirements, and the determination of Ti in the studied samples showed levels of Ti ranging from 0.4 to 3.9 g/kg.